Does astronomy generate economic benefits? Technological innovation seen through the lens of the European Southern Observatory's Very Large Telescope. (1st January 2014) - Fernandes, André; Pessoa, Argentino; Silva, Mário Rui
While the study of the economic impact of big science has been an area of research, there is little work dedicated to the impact of astronomy projects. The present work shows and discusses empirical data concerning the perceived impact by European Southern Observatory's suppliers of collaborating in the construction, update and operation of the Very Large Telescope. Data were obtained through a survey addressed, in 2010, to companies and research centres that supplied the Very Large Telescope between 1998 and 2009. Overall, the present study finds evidence of spillover effects coming from the Very Large Telescope project. Technological excellence and marketing benefits were the spillovers most recognised by suppliers. In general, the perceived impact by companies was lower than that of research centres.